The Impact of Multiple Species Invasion on Soil and Plant Communities Increases With Invasive Species Co-occurrence - Vujanović, Dušanka; Losapio, Gianalberto; Milić, Stanko; Milić, Dubravka (Frontiers in Plant Science, 2022)
Despite increasing evidence indicating that invasive species are harming biodiversity, ecological systems and processes, impacts of multiple species invasion and their links with changes in plant and soil communities are inadequately documented and remain poorly understood. Addressing multiple invaders would help to ward against community-wide, synergistic effects, aiding in designing more effective control strategies. In this work, correlative relationships are examined for potential impacts of three co-occurring invasive plant species, Amorpha fruticosa, Fraxinus pennsylvanica and Acer negundo, on soil conditions and native plant diversity. The research was conducted in riparian ecosystems and included the following treatments: (1) co-occurrence of the three invasive plant species, (2) occurrence of a single invasive species, and (3) control, i.e., absence of invasive species. Co-occurrence of three invasive plant species caused higher direct impact on soil properties, soil functioning and native plant diversity. Soil in mixed plots (those populated with all three invaders) contained higher levels of nitrifying bacteria, organic matter, nitrogen, and carbon as well as lower carbon to nitrogen ratio as compared to single species invaded plots and control plots. Furthermore, native plant diversity decreased with invasive plants co-occurrence. Differences in soil conditions and lower native plant diversity revealed the interactive potential of multiple invasive species in depleting biodiversity and eroding soil functionality, ultimately affecting ecological and biogeochemical processes both below and above ground. Our results highlight the need to prevent the impact of multispecies invasion, suggesting that riparian ecosystems affected by co-occurring invaders should be prioritized for invasion monitoring and ecological restoration.